Harm Reduction Policy Support among Students at Two U.S. Universities. (1st June 2022) - Andraka-Christou, Barbara; Nguyen, Thuy; Harris, Shana; Atkins, Danielle N.; Totaram, Rachel; Golan, Olivia; Koval, Andriy; Madeira, Jody
Abstract: Background: The U.S. is undergoing an opioid overdose crisis. Harm reduction (HR) policies are associated with decreased overdose deaths and incidence of communicable diseases, yet legality of HR policies differs across U.S. jurisdictions. College student perceptions of HR policies are underexplored, even though their voting behavior has increased in recent years. We sought to compare their support of different HR policies and to explore relationships between demographic characteristics and support for HR policies. Methods: We collected cross-sectional, convenience sample survey data from undergraduate students at two large public universities, one in the Midwest and one in the Southeast, during Fall 2018/Spring 2019. We analyzed data using descriptive statistics and logistic regressions. Results: The final sample included 1, 263 respondents. Good Samaritan laws (n = 833, 66%) and naloxone distribution (n = 476, 37.7%) were most commonly supported, while heroin maintenance treatment (n = 232, 18.4%) and heroin decriminalization (n = 208, 16.5%) were least supported. Democrat/liberal or less religious/spiritual respondents supported HR policies more than their Republican/conservative or religious/spiritual counterparts. Midwestern students were more likely to support syringe services programs. Conclusion: HR education initiatives could target religious and/or Republican/conservative students, as they have lower HR support. Among HR policies, Good Samaritan policies may be easiest to pass in college communities.